Sporopollenin, The Least Known Yet Toughest Natural Biopolymer - Mackenzie, Grahame; Boa, Andrew N.; Diego-Taboada, Alberto; Atkin, Stephen L.; Sathyapalan, Thozhukat (Frontiers in Materials, 2015)
Sporopollenin is highly cross-linked polymer composed of carbon, hydrogen and oxygen that is extraordinarily stable and has been found chemically intact in sedimentary rocks some 500 million year old. It is the outer shell (exine) of plant spores and pollen and when extracted it is in the form of an empty exine or microcapsule. The exines resemble the spores and pollen from which they are extracted, in size and morphology. Also, from any one plant such characteristics are incredible uniform. The exines can be used is microcapsules or simply as micron-sized particles due to the variety of functional groups on their surfaces. The loading of the exine microcapsules into their cavities is via multi-directional nano-diameter sized channels. The exines can be filled with a variety of polar and non-polar materials. Such as enzymes can be encapsulated within the shells and still remain active. In vivo studies in humans have shown that an encapsulated active substance can have a substantially increased bioavailability than if it is taken alone. The sporopollenin exine surface possesses phenolic, alkane, alkene, ketone, lactone and carboxylic acid groups. Therefore it can be derivatised in a number of ways, which has given rise to its having been used for, such as, solid supported for peptide synthesis, catalysis and ion-exchange chromatography. Also, the presence of the phenolic groups on sporopollenin endows it with antioxidant activity.